PENGEMBANGAN DIRI: MEMPERSIAPKAN SISWA SMA PGRI 4 PADANG UNTUK MENGHADAPI MASA DEPAN - Izzanil Hidayati; Sartono, Sartono; Putri Sukma Deri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
High School students are individuals who are entering their late adolescence. This adolescence is the stage where individuals decide to continue their education or enter the workforce. High school students should be able to prepare for the future well, and make decisions about their future careers. However, not all students can prepare well for their future career choices. This training aims to increase awareness of SMA PGRI 4 students regarding the importance of having a picture of the future, increase knowledge regarding what to do to plan for the future, information that must be had in planning for the future, and increase student knowledge regarding the importance of involvement in learning and strategies that can be used to be able to undergo the learning process more effectively. The number of participants who attended this training was 34 students, consisting of students in grades XI and XII (23 males; 11 females). The implementation of the training consisted of delivering material from the resource person, followed by small group mentoring activities. The results of the training showed that there were changes in students' attitudes and knowledge after participating in the training activities to prepare for the future (increasing from 83% of students). In addition, there were significant results in the posttest and pretest of training participants (with a significant value of p <,001). After the implementation of the training activities, it is expected that teachers and students can synergize in preparing students' future with more detailed, directed, and clearly measurable preparations.